2017
DOI: 10.1186/s12889-017-4167-1
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study with process evaluation of a preschool intervention to improve child and family lifestyle behaviours

Abstract: BackgroundAround a fifth of children starting school in England are now overweight/obese. There is a paucity of interventions with the aim of obesity prevention in preschool-age children in the UK. Previous research has demonstrated some positive results in changing specific health behaviours, however, positive trends in overall obesity rates are lacking. Preschool settings may provide valuable opportunities to access children and their families not only for promoting healthy lifestyles, but also to develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
3
16
0
1
Order By: Relevance
“…Positive changes to children and parent behaviour was found throughout the examples provided by EYPs. Discussion: EYPs engaged through the FFF programme are actively raising health issues with parents which compares favourably with similar studies where EYPs were found to be reluctant to work with families (5) . A limited variety of strategies were employed to promote behaviour change in parents, which could be addressed by the FFF programme and may support EYPs in overcoming the barriers to parent engagement encountered.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Positive changes to children and parent behaviour was found throughout the examples provided by EYPs. Discussion: EYPs engaged through the FFF programme are actively raising health issues with parents which compares favourably with similar studies where EYPs were found to be reluctant to work with families (5) . A limited variety of strategies were employed to promote behaviour change in parents, which could be addressed by the FFF programme and may support EYPs in overcoming the barriers to parent engagement encountered.…”
Section: Discussionsupporting
confidence: 66%
“…Discussion: Gene-nutrient interaction indicated that folic acid supplements may be required, by some, to overcome inefficient enzymatic function. In the wider literature, the MTHFR genotype has been associated with an 86% increased risk of ASD (5) . Sibling analyses adjust for shared genetics (1) which may explain the null results.…”
Section: An Aetiological Systematic Review and Meta-analysis On The Amentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reliability testing of therapists’ compliance with the protocol by audio/video-taping and evaluation of the classes would have augmented information on fidelity ( Steckler and Linnan, 2002 ). A pilot study or a priori broader stakeholder consultation a priori could have increased institutional support in this trial ( McSweeney et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 Childhood obesity is known to be related to social impairment and low economic productivity in adulthood. 19 Those effects would be more exaggerated in the low socioeconomic community considering many aspects contribute, including lack of parents' attention and care, 20 inability to preserved healthy habits and lifestyles, 21 less educated social groups, 22 and less access to health information.…”
Section: Discussionmentioning
confidence: 99%